Temperature-responsive thermal metamaterials enabled by modular design of thermally tunable unit cells. (March 2019) - Kang, Sunggu; Cha, Jonghwan; Seo, Kyeongbeom; Kim, Sejun; Cha, Youngsun; Lee, Howon; Park, Jinsung; Choi, Wonjoon
Graphical abstract: Highlights: Temperature responsive thermal metamaterials (TMs) comprising of tunable cells were developed. Tunable shifters as unit cells turn on/off anisotropic heat transfer as temperature changes. Tunable shifters were realized in layered structures of metals and phase change nanocomposites. Modular 4-by-4 cells as one TM perform dynamic thermal shielding by temperature changes. The potential use was demonstrated as a tunable interface of thermal dissipation-insulation. Abstract: Integrated circuits or miniaturized portable electronics require adaptive thermal control under certain temperatures. Thermal metamaterials (TMs), which artificially manipulate the heat passing through mediums have shown innovative thermal functions at a continuum scale. However, they cannot implement tunable thermal functions at local spots depending on the operating temperatures. Herein, we introduce temperature-responsive TMs enabled by modular design of thermally tunable unit cells. As ambient temperature changes, tunable thermal shifters can dynamically turn on/off their intrinsic functions to guide anisotropic heat transfer through the transition of thermal conductivities from the inner phase change nanocomposites (PCNCs), and their modular design realizes temperature-responsive thermal shields having switchable functions. The layered structures of stainless steel and the PCNC of n -octadecane embedding carbon nanotubes and copper powder are fabricated as tunable thermal shifters. Their 4 × 4 modular structure confirms the feasibility of temperature-responsive TMs, verified by the disappearance and appearance of thermally shielded regimes at low- and high-temperature ranges. The potential use of the developed concept was demonstrated as tunable interfaces between thermal dissipation and insulation for protecting temperature-sensitive components. This work can offer new capabilities for conventional passive TMs, such as local thermal adaptation, active thermal control interface, and thermal disturbance mitigation.